(3GdOQ GdeNJGQ TQM JfhjQ GdCHUGQs - (3GdMUcaj, YdGA GdOjf, eMeO Hf Ydj Hf eMeO, J (B1088 (3g`s ((3eUWai Hf GdSjO WGdH Hf GdSjO eMeO GdMdHjs)
(3ChdgG (B:s
(3MeO dc jG ef TQMJ UOhQfG HCfhGY GdgOGjI SGHbGs
(3BNQgG (B:s
(3hdG jdRe ehdi GdehdGGI dCfg eSJMb HGdYbO hgh bGFe HgeG aGSJhjG cGdRhLjI aGZJfe gPG GdebGe ef LhGgQ gPG GdcJGH hGddg CYde HGdUhGH (B-s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B6 / 294s
(3eYLe GdeDdajf (B3 / 543s
(3EjVGM Gdecfhf (B1 / 447s
(3gOjI GdYGQajf (B2 / 296s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3Gdabg GdMfHdjs